1995
DOI: 10.1016/1352-2310(94)00313-a
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between surface, free tropospheric and total column ozone in two contrasting areas in South Africa

Abstract: Abstract-Measurements of surface ozone in two contrasting areas of South Africa are compared with free tropospheric and Total Ozone Mapping Spectrometer (TOMS) total column ozone data. Cape Point is representative of a background monitoring station which is remote from pollution impacts, whereas the Eastern Transvaal Highveld (ETH) stations of Elandsfontein and Verkykkop are situated in an area of intense urban and industrial activity. At Cape Point the diurnal cycle in surface ozone is small, the seasonal cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Although there is some variability between the sites, monthly O3 concentrations show a well-defined seasonal variation at all four sites, with maximum concentrations occurring in late winter and spring (August-November). This observed late winter and spring O3 peak are expected for the South African interior as previously reported (Zunckel et al, 2004;Diab et al, 2004;Combrink et al, 1995). These O3 peaks in continental South 30…”
Section: Seasonal and Diurnal Variation Of O3supporting
confidence: 69%
“…Although there is some variability between the sites, monthly O3 concentrations show a well-defined seasonal variation at all four sites, with maximum concentrations occurring in late winter and spring (August-November). This observed late winter and spring O3 peak are expected for the South African interior as previously reported (Zunckel et al, 2004;Diab et al, 2004;Combrink et al, 1995). These O3 peaks in continental South 30…”
Section: Seasonal and Diurnal Variation Of O3supporting
confidence: 69%
“…Combrink et al . [] analyzed surface ozone data from two sites on the Highveld: Elandsfontein in the middle of the industrialized area and Verkykkop that is generally downwind of the industrialized area. They found that on average at both locations, ozone typically peaks between 1400 and 1700 h (local time) due to photochemical formation , which is typical of a polluted environment.…”
Section: Introductionmentioning
confidence: 99%
“…Combrink et al . [] also analyzed monthly surface ozone cycles from 1988 to 1991 and reported maxima in SON and minima in DJF. Rorich and Galpin [] calculated trends of several trace gases at four monitoring stations located in and downwind of the industrialized areas on the Highveld—Elandsfontein, Verkykkop, Palmer, and Makalu—from 1984 to 1994 and found no significant trends in ozone concentrations at all of the sites except Verkykkop.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicated that only 20% of the variances in the TOMS total O 3 data were from variations in tropospheric O 3 , with the remainder possibly because of long-range transport biomass burning. 19 There have been some innovative studies on tropospheric O 3 in the tropics; 20 however, the current errors in TOMS data make it unreliable from 2000 to the present. The new Scanning Imaging Absorption SpectroMeter for Atmospheric Chartography (SCIAMACHY) instrument and OMI may reinvigorate the published projects in this area in the next few years.…”
Section: Regional Air Quality Monitoringmentioning
confidence: 99%